2022
DOI: 10.1002/adsc.202200365
|View full text |Cite
|
Sign up to set email alerts
|

Direct Thioamination of Cyclohexanones via Difunctionalization with Thiophenol and Aniline

Abstract: A synthetic method of o-sulfanylanilines from cyclohexanones, amines, and thiophenols under transition-metal-free conditions is disclosed. This is the first report on the direct thioamination of cyclohexanones via N-iodosuccinimide (NIS) promoted oxidative dehydroaromatization. Non-aromatic cyclohexanones were smoothly dehydrogenated, and acted as an aryl source using oxygen as a green oxidant. The capacity of the resultant o-sulfanylanilines for synthesis of N-arylphenothiazines has been further demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Our continuous interest 9 in aminothiolation reactions led us to envision whether a dehydroaromatizing thioamination of cyclohexanones with primary amines and sodium sulfinates would provide a direct and concise pathway to access significant 1,2-aminothiolated arenes, which are ubiquitous in several pharmaceuticals and bioactive molecules (Scheme 1A). 10 However, this multi-component cascade reaction is a conceptual and underexplored challenge. (1) A compatibility issue exists between deoxygenative thiolation requiring reductive reaction conditions and dehydroaromatization requiring oxidative reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our continuous interest 9 in aminothiolation reactions led us to envision whether a dehydroaromatizing thioamination of cyclohexanones with primary amines and sodium sulfinates would provide a direct and concise pathway to access significant 1,2-aminothiolated arenes, which are ubiquitous in several pharmaceuticals and bioactive molecules (Scheme 1A). 10 However, this multi-component cascade reaction is a conceptual and underexplored challenge. (1) A compatibility issue exists between deoxygenative thiolation requiring reductive reaction conditions and dehydroaromatization requiring oxidative reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research of our group and others has revealed that cyclohexanones and β-tetralones could be coupled with a variety of nucleophiles, including amines, for the synthesis of poly-substituted aromatics and heterocycles via dehydroaromatization. [10,11] Among them, a handful of metalfree difunctionalization of these substrates with various amines were developed with assistance of elemental sulfur and/or iodine, providing o-arylenendiamines, [12] o-sulfanylanilines, [13] phenothiazine, and phenazine derivatives, [14] respectively. However, the multi-functionalization of cyclohexanones and beta-tetralones has so far remained challenging and intriguing.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous groundbreaking achievements have been made, most dehydrogenative functionalizations of cyclohexanone are predominantly focused on the introduction of new functional groups at the carbonyl α- or ipso- positions. In recent years, the dehydrogenation difunctionalization reaction strategy between cyclohexanone and two nucleophilic reagents has been used in the preparation of ortho-disubstituted arenes . As far as we know, a three-component deoxygenation difunctionalization reaction between cyclohexanone, nucleophilic reagents, and electrophilic reagents for preparing ortho-disubstituted arenes has not been achieved.…”
mentioning
confidence: 99%